Effect of Lasalocid on performance of grazing steers - L.R. Corah; Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1982)
Steers fed 200 mg of Lasalocid per day while grazing bromegrass pasture gained 7.6% faster than non-medicated controls; however, this difference was not statistically significant.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Steer; Gain; Performance